2021
DOI: 10.1111/jdv.17302
|View full text |Cite
|
Sign up to set email alerts
|

Lymphogranuloma venereum: a retrospective analysis of an emerging sexually transmitted disease in a Lisbon Tertiary Center

Abstract: Background Lymphogranuloma venereum (LGV) is a sexual transmitted infection (STI), currently endemic within the population of men who have sex with men (MSM) of Western Countries. L2B variant has been reported as the predominant strain in the current LGV epidemics, although a shift towards L2-434 has been observed in some European countries.Objectives To evaluate and characterize the population with LGV infection diagnosed in Centro Hospitalar Universit ario de Lisboa Central, Lisbon, Portugal.Methods A retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 20 publications
0
15
1
2
Order By: Relevance
“…Predictably, this LGV/CT ratio was higher when only anorectal samples were considered (56.5%). Although similar studies have also shown a high percentage of LGV among CT-positive anorectal samples (23% in the recent Portuguese article by Neves et al 1 and 18.7% in another recent French study 8 ), our ratio was substantially higher, which may unveil the importance of this infection in Portugal. A limitation of our study is that analysis of the evolution of LGV prevalence before 2017 was not performed, as we could not retrieve data on the total number of CT tests performed and CT diagnoses before that year.…”
contrasting
confidence: 58%
See 4 more Smart Citations
“…Predictably, this LGV/CT ratio was higher when only anorectal samples were considered (56.5%). Although similar studies have also shown a high percentage of LGV among CT-positive anorectal samples (23% in the recent Portuguese article by Neves et al 1 and 18.7% in another recent French study 8 ), our ratio was substantially higher, which may unveil the importance of this infection in Portugal. A limitation of our study is that analysis of the evolution of LGV prevalence before 2017 was not performed, as we could not retrieve data on the total number of CT tests performed and CT diagnoses before that year.…”
contrasting
confidence: 58%
“…Our LGV patient group demonstrated several similarities to those reported in Europe and Western countries during the ongoing epidemics: most LGV infections occurred in MSM (87%); anorectal mucosa was the most affected location (72.2%), with proctitis being the most common symptom; and there was a high rate of other STIs among LGV-infected patients (46.3%). 1,4,9,10 However, we highlight some unexpected results, such as the fact that 13% of the infections occurred in heterosexuals, a population that is considered at low risk for LGV infection. 11 Whether transmission of LGV from the MSM community to the heterosexual population occurred or distinct transmission networks took place in Portugal, we could not evaluate through the present study.…”
mentioning
confidence: 73%
See 3 more Smart Citations